Application of nonlinear thin-walled elements for analysis of cable-stayed bridges - Guan, Hong; Worsak Kanok-Nukulchai; Pisidhi Karasudhi; Yamaguchi, Hiroki; German Academic Exchange Service (DAAD) (Bangkok : Asian Institute of Technology, 1992)
In this paper, application of the recently developed linear and nonlinear degenerated thin-walled element are presented through the analysis of cable-stayed bridge. The three-dimensional behavior of cable-stayed superstructure can be satisfactorily represented and the analysis is greatly simplified by using the efficient flexural-torsional thin-walled element with consideration of effects of warping restrained conditions. The linear and nonlinear analyses of long-span cable-stayed bridges are pe1formed under the effect of symmetric and eccentric loading. The sources of geometric nonlinearity, such as beam-column effect in deck and tower, cable sag, and change of the bridge geometry due to large displacements, are considered in the analysis. Special ·ruTangements for the compatibility of bridge deck and the cable are discussed. Several examples of cable-stayed bridges demonstrate the effectiveness of the present model of thin-walled elements.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Thin-walled structures; Bridges, Cable-stayed